STRATEGI PEMBELAJARAN KITAB KUNING DI MBI MAMBAUL FALAH SOKAONENG - Abd. Hadi Rohmani (Sekolah Tinggi Agama Islam Hasan Jufri Bawean, 2022)
This article aims to conduct a comprehensive study of the yellow book learning strategy applied at MBI Mambaul Falah Sokaoneng Tambak Gresik. It is common knowledge that studying and understanding the yellow book is not an easy thing. The difficulty is because the yellow book which is a religious source of Islam is written in Arabic and in a typical pre-modern format. However, these difficulties can be overcome if the asatidz have the right strategies so that they can make the learning process effective and efficient. It is MBI Mambaul Falah Sokaoneng, located in Tambak sub-district, Gresik district, who succeeded in sending some of its students to a book reading competition throughout the province of East Java and has been the best participant several times by winning the championship. This research is a type of field research and is carried out with a qualitative approach. The results of this study indicate that there are several strategies used by MBI Mambaul Falah to improve the mastery and understanding of the students in learning the yellow book. Some of the strategies in question are: choosing learning methods, bahtsul masail and online discussions attended by students, alumni, guardians of students and sympathizers, granting permission to use laptops and cell phones, adequate facilities, pleasant environment, musyrif standby, and building interest. and students' learning motivation.